2016
DOI: 10.1007/s10964-016-0490-6
|View full text |Cite
|
Sign up to set email alerts
|

Paternal Monitoring: The Relationship Between Online and In-Person Solicitation and Youth Outcomes

Abstract: Despite extensive literature on parental monitoring, few studies have focused on father-youth solicitation in particular and none on solicitation via communication technology. To address this gap, this study explored the relationships between fathers' online and in-person solicitation of their adolescent and emerging adult children, and the youth's internalizing, externalizing, and prosocial behaviors. A sample of US fathers (N = 158) reported on solicitation patterns, use of technology, and their child's beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 55 publications
(103 reference statements)
1
21
0
2
Order By: Relevance
“…Despite these opportunities for text messaging to facilitate the development of autonomy from parents, there is also the potential for it to impair this developmental process if parents use texting as a way to drastically increase their oversight. In line with this, a few studies have found that the expectation of continuous contact is a source of conflict among adolescent–parent relationships (Blackwell, Gardiner, & Schoenebeck, ) and parents’ digital solicitations for information are less effective than in‐person soliciations (Hessel, He, & Dworkin, ). This suggests that although text messaging has the potential to promote autonomy, excessive parental contact via text might inhibit it.…”
Section: Developmental Tasks Of Adolescencementioning
confidence: 83%
See 1 more Smart Citation
“…Despite these opportunities for text messaging to facilitate the development of autonomy from parents, there is also the potential for it to impair this developmental process if parents use texting as a way to drastically increase their oversight. In line with this, a few studies have found that the expectation of continuous contact is a source of conflict among adolescent–parent relationships (Blackwell, Gardiner, & Schoenebeck, ) and parents’ digital solicitations for information are less effective than in‐person soliciations (Hessel, He, & Dworkin, ). This suggests that although text messaging has the potential to promote autonomy, excessive parental contact via text might inhibit it.…”
Section: Developmental Tasks Of Adolescencementioning
confidence: 83%
“…These findings are in line with other studies examining other digital media platforms. In general, parental monitoring via a wide range of digital technologies is less effective than in‐person communication (Hessel et al, ; Rudi & Dworkin, ). If parents use their adolescents’ phones as a means of surveillance by tracking children’s locations or expecting constant communication, this could thwart the development of autonomy.…”
Section: Discussionmentioning
confidence: 99%
“…Further research examining parenting practices, especially the role played by fathers is required, as the vast majority of research to date has focused on mothers (Hessel et al, 2016). Additionally, a more fine-grained analysis of parental practices is required, that differentiates between parents use of technology generally and the use of technology for parenting (Walker and Rudi, 2014), with future research considering how these different uses of technology may influence parenting styles, the nature and degree of internet mediation and the digital ethos of the home in general.…”
Section: Understanding Contextual Influencesmentioning
confidence: 99%
“…Although the use of technology for parenting has become nearly ubiquitous (Walker, Dworkin, & Connell, ), we know little about the outcomes of online parenting behaviors. Hessel, He, and Dworkin () found that although fathers were using technology to solicit information from their adolescent, solicitation of information online was positively associated with internalizing and externalizing problems and negatively associated with prosocial behaviors in adolescents. This is in stark contrast to soliciting information from adolescents in person, which showed the opposite relationships.…”
Section: Integration and Discussionmentioning
confidence: 99%